Differences in the Iconography of the Plot the Last Supper in the Illuminations of the Gospels and Psalters of the 10th – 14th Centuries Created in the Byzantine Empire - Nataliia Dmytrenko (Anastasis: Research in Medieval Culture and Art, 2021)
The purpose of this study is to find and highlight the most striking pieces of the Last Supper in the examples of the Gospels and Psalters created on the territory of the Byzantine Empire in the 10th – 14th centuries, as well as to analyse the iconography and trace the development of the plot over the centuries. The study reflects the following aspects: how the early Christian sources influenced the formation of this plot and how long they continued to exist, what sources the masters employed to create these works, and how individual artistic details and elements pass from one work to another.